USES OF COLOURS: IN THEORY & APPLICATION - Bisht, Aekta; Garhwal, Srinagar (International Journal of Research -GRANTHAALAYAH, 2014)
Pigments, colours and mediums are the tools of an artist. Ever since human beings stood upright, freeing their hands, they have been using natural pigments, earth colours and synthetic pigments to record their experiences. If the language is meant to communicate ideas and record events, then art was truly yhe first language. Colour is the most immediate form of non- verbal communication. We naturally react to colour as we have evolved with a certain understanding of it, partly because the survival of our ancestors depended on it with regard to what to consume and avoid. Colour is used to represent thoughts and emotions in a way that no other element of design can, and it can act as an instant attention grabber whether in print, on screen or on a supermarket shelf. As such, colour is an important face og contemporary design. We all, inherently, have preferences that inform our decisions when dealing with colour, and we are subject to all the cultural norms and understandings of colour usage that surround us.